Understanding the Impact of Drought on Foliar and Xylem Invading Bacterial Pathogen Stress in Chickpea - Sinha, Ranjita; Gupta, Aarti; Senthil-Kumar, Muthappa (Frontiers in Plant Science, 2016)
In field conditions, plants are concurrently exposed to multiple stresses, where one stressor impacts the plants’ response to another stressor, and the resultant net effect of these stresses differs from individual stress response. The present study investigated the effect of drought stress on interaction of chickpea with Pseudomonas syringae pv. phaseolicola (Psp; foliar pathogen) and Ralstonia solanacearum (Rs; xylem inhabiting wilt causing pathogen), respectively, and the net-effect of combined stress on chlorophyll content and cell death. Two type of stress treatments were used to study the influence of each stress factor during combined stress, viz., imposition of drought stress followed by pathogen challenge (DP), and pathogen inoculated plants imposed with drought in course of pathogen infection (PD). Drought stress was imposed at different levels with pathogen inoculum to understand the influence of different stress intensities on stress interaction and their net impact. Drought stressed chickpea plants challenged with Psp infection (DPsp) showed reduced in planta bacterial number compared to Psp infection alone. Similarly, Rs infection of chickpea plants showed reduced in planta bacterial number under severe drought stress. Combined drought and Psp (DPsp) infected plants showed decreased cell death compared to plants infected only with Psp but the extent of cell death was similar to drought stressed plants. Similarly, chlorophyll content in plants under combined stress was similar to the individual drought stressed plants; however, the chlorophyll content was more compared to pathogen only infected plants. Under combined drought and Rs infection (DRs), cell death was similar to individual drought stress but significantly less compared to only Rs infected plants. Altogether, the study proposes that both stress interaction and net effect of combined stress could be majorly influenced by first occurring stress, for example, drought stress in DP treatment. In addition, our results indicate that the outcome of the two stress interaction in plant depends on timing of stress occurrence and nature of infecting pathogen.